Limited Innovations After More Than 65 Years of Immunoglobulin Replacement Therapy: Potential of IgA- and IgM-Enriched Formulations to Prevent Bacterial Respiratory Tract Infections - Langereis, Jeroen D.; van der Flier, Michiel; de Jonge, Marien I. (Frontiers in Immunology, 2018)
Patients with primary immunoglobulin deficiency have defects in immunoglobulin production or maturation, which makes these patients more susceptible to bacterial infection. Most prevalent are the selective IgA deficiencies (~1:3.000), followed by common variable immune deficiency (~1:25.000). Agammaglobulinemia is less common (~1:400.000) and is characterized by very low or no immunoglobulin production resulting in a more severe disease phenotype. Therapy for patients with agammaglobulinemia mainly relies on prophylactic antibiotic and the use of IgG replacement therapy, which successfully reduces the frequency of invasive bacterial infections. Currently used immunoglobulin preparations contain only IgG. As a result, concurrent IgA and IgM deficiency persist in a large proportion of agammaglobulinemia patients. Especially patients with IgM deficiency remain at risk for recurrent infections at mucosal surfaces, which includes the respiratory tract. IgA and IgM have multiple functions in the protection against bacterial infections at the mucosal surface. Because of their polymeric structure, both IgA and IgM are able to agglutinate bacteria efficiently. Agglutination allows for entrapment of bacteria in mucus that increases clearance from the respiratory tract. IgA is also important for blocking bacterial adhesion by interfering with bacterial adhesion receptors. IgM in its place is very well capable of activating complement, therefore, it is thought to be important in complement-mediated protection at the mucosal surface The purpose of this Mini Review is to highlight the latest advances regarding IgA- and IgM-enriched IgG replacement therapy (IgGRT). We describe the different IgA- and IgM-enriched IgG formulations, their possible modes of action and potential to protect against respiratory tract infections in patients with primary immunoglobulin deficiencies.